2021
DOI: 10.1101/2021.07.05.21260014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenome-wide DNA methylation profiling of healthy COVID-19 recoverees reveals a unique signature in circulating immune cells

Abstract: Background: Coronaviruses such as SARS-CoV-2 may circumvent host defence mechanisms by hijacking host proteins, possibly by altering DNA methylation patterns in host cells. While most epigenetic studies have been performed in severely ill COVID-19 patients, studies on individuals who have recovered from mild-to-moderate disease remain scarce. The aim of this study was to assess epigenome-wide DNA methylation patterns in COVID-19 convalescents compared to uninfected controls from before and after the pandemic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Differential DNA methylation profiles differentiate COVID-19 recuperation from uninfected controls. Differential DNA methylation patterns associated with Wnt, mAChRs signaling, and GnRH receptor pathways (Huoman et al, 2021). SARS-CoV-2-negative vs. SARS-CoV-2-positive cases (Spain).…”
Section: Covid-19 Patients With Different Disease Severity Vs Healthy...mentioning
confidence: 99%
“…Differential DNA methylation profiles differentiate COVID-19 recuperation from uninfected controls. Differential DNA methylation patterns associated with Wnt, mAChRs signaling, and GnRH receptor pathways (Huoman et al, 2021). SARS-CoV-2-negative vs. SARS-CoV-2-positive cases (Spain).…”
Section: Covid-19 Patients With Different Disease Severity Vs Healthy...mentioning
confidence: 99%
“…Comprehensive transcriptomic analysis of multiple infected cell lines and COVID-19 patient-derived samples combined with pathway enrichment analysis implicated over 60 epigenetic response proteins that are relevant to SARS-CoV-2 infection [ 91 ]. Additionally, differential DNA methylation patterns in immune cells that distinguish COVID-19 convalescents from uninfected controls have been reported [ 92 ]. Finally, changes in host 3D chromatin architecture upon SARS-CoV-2 infection have been assessed by in situ Hi-C. Quantification of the pairwise interactions between chromosome regions showed that SARS-CoV-2 infection alters host chromosome organization to induce certain pro-inflammatory genes and suppress antiviral interferon-responsive genes [ 93 ].…”
Section: Sars-cov-2mentioning
confidence: 99%